ANALYSIS OF STUDENTS’ PERSPECTIVE ON COMPETENT AND PROFESSIONAL ENGLISH TEACHERS IN GRADE NINTH OF SMP WR. SUPRATMAN 1 MEDAN 2024/2025 ACADEMIC YEAR - Rena Agus Prayana Br Tarigan; Princesscia Aulia Ryantono; Kresna Ningsih Manik (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2024)
This qualitative study examines ninth-grade students’ perspectives on the Competence and Professionalism of English teachers at SMP WR. Supratman 1 Medan during the 2024/2025 academic year. The study addresses three central questions: (1) How do students perceive professional and competent English teachers? (2) How are these traits demonstrated in teachers’ practices? (3) What are the reasons behind these perceptions? The primary data collection method involves administering surveys and questionnaires, consisting of both closed-ended and open-ended questions. Preliminary thematic anaylsis reveals that students highly value teachers’ pedagogical adaptibility and emotional support, while also recognizing the influence of contextual factors, such as the classroom environment, on their perceptions. This study highlights the dynamic interaction between teacher competence and student learning experiences, providing recommendations for teacher training programs to better meet the needs of learners.